How Uzbek mass media re-shapes English loanwords - Chorieva , Asila; Dalieva , Madina Khabibullaevna (The Lingua Spectrum, 2026)
Changes in English loanwords in Uzbek mass media are not only a question of “more borrowings.” They are changes in channel (from Russian-mediated forms to direct English-oriented intake), form (parallel Latin/Cyrillic spellings and unstable transliteration), and integration (Uzbek affixation, hybrid formations, and meaning shifts). I treat mass media broadly – online news, platform-linked journalism, and public-facing commentary – because newsroom language now circulates inside the same digital ecosystems that generate new lexemes. Recent Uzbek scholarship using corpus-based data from social media, news websites, and forums shows rapid diffusion of English-origin items and their adaptation through phonological and morphological mechanisms (e.g., “smartfon”, “kompyuterlashtirish”). At the same time, public debate in Uzbekistan highlights the lack of consensus on foreign-word orthography and the costs of relying on intermediary-language spellings. The article argues that the most visible “change” today is the move from borrowing-as-import to borrowing-as-productive material for Uzbek word-formation and media pragmatics.